Analisis Faktor Organisasi dalam mengatasi Technostress pada Karyawan - Evita Ilma Elina Sari; Diah Priharsari; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Technology and information systems also have potential weakness that can be associated with negative stress. Stress caused by the utilization of technology is called technostress. Extreme technostress can cause employees get tired at work, unpleasant experience or dissatisfaction, and the emergence of a desire to stop working which will certainly harm the company. Therefore, this research was conducted with the aim of knowing how technostress is experienced by employees and how an organization can overcome technostress. The case study that used is the Education Personnel from Faculty of Computer Science Brawijaya University. Collecting data in this study using semi-structured interviews then will be transformed in verbatim. Data that collected will be processed using qualitative analysis with thematic analysis method. The conclusion of this study, there are eleven codes that explain the technostress experienced by employees and how an organization can overcome it. Codes that describe technostress experienced by employees are information systems to support employee work, information systems to support employee communication, techno overload, techno uncertainty, techno invasion, and techno insecurity then the code that used by organizations or companies to overcome technostress is the provision of technical support, literacy of facilities, involvement of facilities, and providing motivational encouragement. This results has important implications for a company to manage the technostress.